Göç Kuramları ve Sosyal Hizmet Yaklaşımları - Apak, Hıdır; Cete, Halime (Göç ve Sosyal Hizmet, 2023)
Migration, which is the main actor in the process of social change and is gradually increasing, appears as an indispensable element of the global world. Throughout history, people have changed their places for various purposes. In the past, these displacements have mostly been interpreted as individual reasons. However, the migration in question is too complex and multifaceted to be reduced to individual reasons. There are some classifications in migration theories created to understand, define, classify and predict migration due to the complex and multifaceted nature of migration. These include economic, historical-structuralist, social, cultural, initiator and sustainer of migration. Nevertheless, these classifications have not been generally accepted. Because migration is differentiated as micro, meso, macro dimensions and national and international migration. This makes it very difficult to have a general acceptance for migration theories. For this reason, the study includes basic migration theories rather than categorised migration theories. In addition, social service approaches that help migrant applicants are also put forward. Social work with migrants is essential in understanding and making sense of migration theories. Social work, as a profession that has adopted social justice, human rights and respect for differences as a principle, should not be considered separately from the migrant who is the subject of migration. In this respect, the main emphasis in this study is on human rights, anti-oppression and ethnic sensitivity. In general terms, the study tried to explain the fundamental ten migration theories and included three approaches that are directly related to the migrant applicant from social work approaches. This study aims to present the basic theories of migration and to explain some social work approaches in this context. As a result of the study, it was understood that there is no general migration theory in understanding migration, many migration theories emerged in response to each other, and the importance of migrant-oriented social work approach for migration management was emphasised.